Nanocrystal Grain Growth and Device Architectures for High-Efficiency CdTe Ink-Based Photovoltaics - Crisp, Ryan; Panthani, Matthew G.; Rance, William L.; Duenow, Joel N.; Parilla, Philip A.; Callahan, Rebecca; Dabney, Matthew S.; Berry, Joseph J.; Talapin, Dmitri V.; Luther, Joseph M. (Acs Nano, 2014)
We study the use of cadmium telluride (CdTe) nanocrystal colloids as a solution-processable "ink" for large-grain (die absorber layers in solar cells. The resulting grain structure and solar cell performance depend on the initial nanocrystal size, shape, and crystal structure. We find that inks of predominantly wurtzite tetrapod-shaped nanocrystals with arms similar to 5.6 nm in diameter exhibit better device performance compared to inks composed of smaller tetrapods, irregular faceted nanocrystals, or spherical zincblende nanocrystals despite the fact that the final sintered film has a zincblende crystal structure. Five different working device architectures were investigated. The indium tin oxide (ITO)/CdTe/zinc oxide structure leads to our best performing device architecture (with efficiency >11%) compared to others including two structures with a cadmium sulfide (CdS) n-type layer typically used in high efficiency sublimation-grown (die solar cells. Moreover, devices without CdS have improved response at short wavelengths.
Keywords: CdTe; photovoltaic; nanocrystal; grain growth; device architecture; sintering; solution-processed